Pengembangan Penuntun Praktikum Berbasis Inquiry pada Mata Kuliah Biologi Umum - Eko Wulandari (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to develop an Inquiry-based practicum guide in the General Biology course to strengthen General Biology trial or practicum skills further. The method used in this research is Research and Development. The results showed that this practicum guide was included in the very valid category with a percentage of 86, which was in the range of 81-100. In conclusion, the Inquiry-based practicum guide developed in General Biology courses is valid and can be used in other General Biology practicums that use the same material. Keywords: General Biology, Inquiry, Practical Guide